Hubungan Gaya Komunikasi Pemimpin dengan Kinerja Karyawan PT. Socfin Indonesia Perkebunan Tanah Besih Serdang Bedagai Sumatera Utara - MUNTHE, AQIL DWI PUTRA; SUARDI, I DEWA PUTU OKA; ASTITI, NI WAYAN SRI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Relationship between Leader's Communication Style and Employee Performance of PT. Socfin Indonesia Plantation Tanah Beih Serdang Bedagai North Sumatra The performance of each employee in each division is highly dependent on the communication style of the leader of the division head. Differences in leadership style of communication often lead to jealousy between divisions. In addition, based on observations made at PT. Socfin Indonesia Plantation Tanah Besih Serdang Bedagai, North Sumatra, the performance of the employees is considered to be lacking. The purpose of this study was to determine the leadership communication style, employee performance, and the relationship between leadership communication style and employee performance at PT. Socfin Indonesia, Serdang Bedagai Land Plantatio n, North Sumatra. The population in this study were 226 people. Sampling using the Slovin formula so that the number of respondents in this study were 69 employees with descriptive research methods and data analysis used was descriptive analysis and statistical correlation analysis. The results of this study indicate that the leadership communication style has a positive and significant relationship with the performance of employees of PT. Socfin Indonesia Perkebunan Tanah Besi, Serdang Bedagai, North Sumatra, amounted to 67,6%, this is assumed based on the results of the correlation test with the acquisition of the correlation coefficient value obtained at 0,676 with a sig value. (2-tailed) of 0,00 < 0,05 and the results of the linearity test with an F value of Linearity of 66,30 > F table 3,13 with a significance value of 0,00 < 0,05. The leader's communication style has a score between 139-276 which means that the leader's communication style in the category is good enough to be good enough with respondents who responded well enough as many as 18 people (26,1%) who gave good responses as many as 18 people (26,1%). Employee performance had a score between 139-276 in the category good enough to good with respondents giving a fairly good response of 18 people (26,1%) who gave good responses as many as 18 people (26,1%).